SAFETY INDICATORS OF MELANIN AS AN INGREDIENT OF CONFECTIONERY SEMIFINISHED PRODUCTS - M. N. Shkolnikova; E. A. Kadritskaya (Современная наука и инновации, 2022)
Research on the search for alternatives to cocoa powder requires not only an assessment of the technological adequacy of new ingredients, but also confirmation of their safety. The results of safety indicators of samples of melanin and cocoa powder are presented. It is shown that the melanin prototype obtained from buckwheat husks exceeds the control samples in all the studied indicators, which makes it possible to use it as part of cocoa-containing glazes, including at catering establishments, for the ingredients of which potentially dangerous factors have been identified and measures have been proposed to prevent their occurrence.